2014
DOI: 10.1021/mz500656g
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Polymers à la Carte from Time-Controlled Direct (Hetero)Arylation Polymerization

Abstract: Direct (hetero)arylation polymerization (DHAP) shows great promise for simple, cheap, and environmentally benign preparation of conjugated polymers, but seems to involve a lack of selectivity when different aromatic C–H bonds are present. We report that some time-controlled DHAP reactions can yield well-defined and processable semiconducting polymers. Following these procedures, various aromatic compounds have been efficiently polymerized, including 2,7-dibromofluorene, 2,7-dibromocarbazole, 1,4-dibromobenzene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
168
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 104 publications
(176 citation statements)
references
References 33 publications
6
168
2
Order By: Relevance
“…These results show again that these general DHAP conditions cannot be easily applied for the coupling of nonprotected thiophene units. 12 It is also interesting to note that solid-state optical and thermal measurements seem more sensitive to the presence and detection of structural defects than 1 H NMR analyses in solution. These features could indicate that minor molecular defects can induce important changes within the supramolecular organization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results show again that these general DHAP conditions cannot be easily applied for the coupling of nonprotected thiophene units. 12 It is also interesting to note that solid-state optical and thermal measurements seem more sensitive to the presence and detection of structural defects than 1 H NMR analyses in solution. These features could indicate that minor molecular defects can induce important changes within the supramolecular organization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…12 Those conditions involving a palladium source, a tris(o-anisyl)-phosphine ligand, cesium carbonate, pivalic acid in toluene or THF were successfully applied to dibromo-6,6′-isoindigo derivatives as well. 13 In these cases, the resulting copolymers showed comparable, if not slightly better, properties when compared to their Suzuki-synthesized analogues.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This novel method allows the formation of carbon–carbon bonds between simple (hetero)arenes and (hetero)aryl halides, saving simultaneously many synthetic and tedious purification steps. Moreover, it has been shown that DHAP, when carefully optimized, can lead to improved molecular weights along with better overall yields …”
Section: Introductionmentioning
confidence: 99%
“…The polymerization conditions utilized here are based on a recent report which has shown a high selectivity between aryl-bromide and non-substituted thiophene units. [ 29 ] Suzuki cross-coupling polymerization reactions were also performed for comparison purposes (see the Supporting Information). All polymers are soluble in common chlorinated solvents, such as chloroform (CF) and o -dichlorobenzene (ODCB), as well as chlorine-free solvents such as o -xylene.…”
mentioning
confidence: 99%